2021
DOI: 10.1108/ijccsm-08-2020-0090
|View full text |Cite
|
Sign up to set email alerts
|

Natural disaster shock, risk aversion and corn farmers’ adoption of degradable mulch film: evidence from Zhangye, China

Abstract: Purpose Degradable mulch film (DMF) is a potential alternate to polyethylene (PE) mulching. In this regard, the purpose of this paper is to explore the effects and paths of natural disaster shock and risk aversion influencing farmers’ DMF adoption. Design/methodology/approach This research is conducted by collecting cross-sectional data of corn farmers in Zhangye, China. First, by using the Tobit model, the paper attempts to explore the effects of natural disaster shock and risk aversion influencing farmers’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…More economic growth leads to more income that leads to more environmentally friendly sources of energy for goods production. The results are consistent with the findings of Aziz et al [81], Si et al [82,83], and Koondhar et al [84]. In the case of BRICS and the MINT panel, Aziz et al [85,86] revealed that countries, after attaining a certain level of income, are inclined to regenerate the environment.…”
Section: Main Regression Resultssupporting
confidence: 89%
“…More economic growth leads to more income that leads to more environmentally friendly sources of energy for goods production. The results are consistent with the findings of Aziz et al [81], Si et al [82,83], and Koondhar et al [84]. In the case of BRICS and the MINT panel, Aziz et al [85,86] revealed that countries, after attaining a certain level of income, are inclined to regenerate the environment.…”
Section: Main Regression Resultssupporting
confidence: 89%
“…Besides, the resource wastes and environmental pressures caused by the continuous growth of grain production in major producing areas (Yang et al, 2021;Li and Lin, 2022), arouse more attention to the coordinated use of various green technologies. Additionally, the influence paths of green technology on the promotion of GTFPG also vary in different areas, due to regional differences in development and applicability of green technologies (Si et al, 2021;He et al, 2021). The standard error of coefficient estimation is shown in brackets, '*', '**', '***' represent the significance levels of 10%, 5% and 1%, respectively; "-" represent no data.…”
Section: Discussionmentioning
confidence: 99%
“…However, agriculture is significantly affected by natural factors such as weather and climate [5], and the supply chain of agricultural products carries the risk of output uncertainty [6]. In practice, farmers' production and operation scales are small, and they are risk-averse to output uncertainty [7,8]. Farmers' risk-averse attitude affects the equilibrium decision-making of supply chain members [9].…”
Section: Introductionmentioning
confidence: 99%